Stratification, sex and ontogenetic effects on the lipid and fatty acid profiles in the blubber of sperm whales from Tasmanian waters - Jackson, CH; Gales, R; Patti Virtue; Peter Nichols (2022)
We examined the differential deposition of lipids according to layer, sex and ontogeny in the blubber of 31 adult sperm whales (n = 22 females, 9 males) and two calves that stranded off the Tasmanian coast from 2002 to 2004. Total lipid (TL) content varied widely across the blubber layers of adults (27–77%). Overall, females had higher TL content than males possibly representing higher energy needs due to reproduction. Higher TL content in the middle layer of adults (69%) suggests this layer may act as an energy reserve. Wax esters (WE) dominated the blubber and were highest in the outer layer of adults and calves, likely providing insulative qualities for this deep-diving odontocete. Triacyclglycerols, an easily mobilized energy source, were highest in the inner layer of females (37.3 ± 13.5%) and calves (32.1 ± 1.8%) compared to males (17.1 ± 8.2%). Monounsaturated fatty acids (MUFA) also dominated the blubber. An increasing gradient from the inner to outer layer reflected an increasing source of endogenously synthesized lipids, whereas an increasing gradient of saturated fatty acids and polyunsaturated fatty acids (PUFA) toward the inner layer reflected an increasing source of dietary lipids. Although body site did not affect lipid profiles, stratification between the outer and more metabolically active inner layers suggests that only using the outer layer may result in an incomplete lipid profile for sperm whales.